Validation of custom wearable sensors to measure angle kinematics: A technical report - Walmsley, C.; Xu, Weiyang; Ortega-Sanchez, Cesar; Campbell, Amity; Imms, C.; Elliott, Catherine (Springer Berlin Heidelberg, 2019)
The objective of this study was to determine the accuracy of custom designed wearable sensors when compared to a robotic device to measure i) peak angles in a single plane (flexion/extension) and ii) the extent of error associated with speed of movement. Two experimental procedures were undertaken; i) one wearable sensor was mounted on the arm of a step motor that simulated wrist flexion/extension at the speed of 90°/s with the other wearable sensor static (flat surface); and ii) two wearable sensors were each mounted on a step motor which was programmed to move at two movement speeds 30°/s and 90°/s. When compared to pre-determined angles of the robotic device, the wearable sensors detected peak angles with mean error ranging from -0.95° to 0.11° when one wearable sensor was static and the other dynamic. When two wearable sensors were moving, movement at the higher speed (90°/s) had a mean error range of -2.63° to 0.54, and movement at the slower speed (30°/s) had a mean error range of -0.92° to 2.90°. The custom wearable sensors demonstrated the ability to measure peak angles comparable to the robotic device and demonstrated acceptable to reasonable error when tested at two movement speeds. The results warrant future in vivo testing.